Konsumsi Transfer Factor Belle Vie Pada WUS Dengan Gangguan Menstruasi Di Kota Makassar - Novitasari, Kesna Nathasya; Nurlinda, Andi; ahri, Reza aril (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2018)
Reproductive age women having lots of menstrual problems or abnormal menstruation, such as menstrual syndrome and irregular menstruation. This research aims to review and analyze in-depth information regarding the effectiveness of the consumption of the Transfer Factor Belle Vie Against menstrual disorders in women age early. The method of this research is qualitative research using the descriptive analysis. Engineering data collection using the dwarf in-depth interview (in-depth interviews) as well as the documentation continuously as long as the research progresses. The results of this study indicate that menstrual disorders experienced by the informant. That is the pain at the time of menstruation, menstrual blood is too many and manifest irregularities of menses. Knowledge of the informant about menstrual disorders if you have menstrual irregularities each month and menstruation is prolonged and the factors that affect the onset of menstrual disorders are factors of nutrient intake, stress, work, physical activity, and obesity. Way or attempt the informant in tackling menstrual disorders there are soon check into medical facilities, given hormone therapy, conducted a pap smear. The dangers that can be caused by menstrual disorders could hit polyps, myomas, cancer, and tumors. Daily habits such as diet, exercise habits, the activity can also affect the menstrual disorders. TF Bellevie according to informants quite effective in dealing with menstrual disorders, with the regularity of consuming and appropriate recommended dose. Consume TF Bellevie continuously also does not cause any side effects and harm against women's reproductive organs. Menstrual disorders experienced by women of fertile age should advance in advance by a doctor so it can determine the proper care for reproductive health although TF Bellevie quite effective in tackling the problem.